Minimization of direct costs in the construction of torrent control structures - Nada Dragović; Tijana Vulević; Mirjana Todosijević; Stanimir Kostadinov; Miodrag Zlatić (Tehnički Vjesnik, 2017)
The most important elements in the planning of the implementation of the torrent (flood) control projects which need to be estimated are time, costs (budget) and resource required. These three elements are interactive: a shorter duration of structure construction causes additional resources engagement and increased costs, and vice versa - greater costs provide a shorter duration of construction. This paper analysis direct project cost minimization for four torrent control projects. The construction duration and the dynamic plan of project activities have been determined using the CPM method of network planning. The optimization problem – minimization of direct cost of construction subject to constraints such as: given deadline, precedence constraints, and upper and lower bounded duration time of activities is solved using linear programming and Matlab toolbox. Our results show that applied methods ensure significant cost savings, which is an important challenge in the construction management.